Pengaruh Kebijakan Desentralisasi Fiskal Pada Kemandirian dan Kesejahteraan Masyarakat di Kecamatan Gondangrejo Kabupaten Karanganyar - Hidayat, Muhammad Ridwan Nur; Arif, Muhammad (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2023)
This study aims to analyze the relationship between the Village Fund and the Village Building Index and the Level of Welfare in Gondangrejo District. In this study, the analytical tool used is panel data analysis with two econometric models in 13 villages in Gondangrejo District within a period of 5 years from 2016 to 2020. The type of data used in this study is secondary data in the form of panel data (a combination of time series with a cross section) in the form of Village Fund data, the Village Building Index(IDM) and the Level of Community Welfare of 13 villages in Gondangrejo District. Data were obtained from the Regent's Regulation, Village Information System (Kemendesa), IDM, and BPS. The results of the two models show that the Village Fund plays a role in the level of independence of villages in Gondangrejo District, Karanganyar Regency.